Dayara bugyal restoration model in the alpine and subalpine region of the Central Himalaya: a step toward minimizing the impacts - Jagdish Chandra Kuniyal; Priyanka Maiti; Sandeep Kumar; Anand Kumar; Nisha Bisht; K. Chandra Sekar; Satish Chandra Arya; Sumit Rai; Mahesha Nand (Scientific Reports, 2021)
Abstract Eco-restoration initiative work in the high altitude Dayara pastureland (3501 m) from the Indian Himalayan Region has been considered to be one of the successful field demonstration against both natural and anthropogenic degradation. The present study therefore attempts to assess the implications of entire eco-restoration model as practiced by Department of Forest, Government of Uttarakhand in 2019. Its assessment was done by calculating restoration success index by way of considering three categories, viz., direct management measure (M), environmental desirability (E) and socio-economic feasibility (SE) considering 22 individual variables. ‘M’ comprised both biotic and abiotic pressures. Grazing and tourism were biotic, while abiotic pressure was considered mainly soil erosion in alpine area due to topographic fragility. Above ground vegetation profile and below ground soil nutrient profile (N, P, K, pH and water holding capacity) were analyzed in ‘E’ component. In the last but not least, ‘SE’ was analyzed to assess the social acceptability of the local communities and stakeholders who are supposed to be ultimate beneficiary of alike interventions. Direct management measure was found with the variable index score of 0.8 indicating the higher score as compared to environmental desirability (0.56). Under direct management measure, grazing and tourists’ carrying capacity of the area was analyzed with high management needs to call the region sustainable in terms of availability of bio-resources. The ecosystem index score was evaluated for the reference (81.94), treated (64.5) and untreated zones (52.03), wherein increasing profile of these values were found. The outcomes like improved vegetation profile in terms of total herb density, soil nutrient profile of the restored area along with soil pH (4.96) and water holding capacity (49.85%) were found to be restored significantly along with controlling 169.64 tonne year-1 soil erosion from draining. The assessment of grazing pattern of 118 migratory Cow Unit (CU) (76 horse/mule and 18 sheep/goat, already controlled), 318 local CU (30 horse/mule and 187 sheep/goat) were calculated and recommended to be controlled. Tourists’ carrying capacity of 274 tourists per day and manual removal of Rumex nepalensis at the shepherd camping site were found to be worth to apply in the area. Use of biodegradable but locally sourced material and engaging local villagers in this endeavor were also found to be in harmony with SDG Goal 1 (no poverty). Therefore, the restoration and its evaluation model could have its future prospects to prove as a successful restoration practice. This restoration practice could not only be worth in high altitude degraded alpine pastures of the Indian Himalayan Region but also to other mountain alpine and sub-alpine ecosystems.